Visualization analysis and design of DDoS attack - Yi-fan ZHANG; Xiao-ju DONG (网络与信息安全学报)
Firstly, the IP address of the Web log were visualized, and an integral system was presented by using proper visualization methods. Secondly, the whole system was related to the IP address, containing source IP address, target IP address and their relationship respectively. It provided users with different views of data, which could show more details and undetected relations among massive data. Besides, some interactions were added into the system, which made it more effective and useful. Finally, it ended up with the comparison of the systems when loading data with the DDoS attack and without it. It made much sense in the application field.